Unwanted visionaries the Soviet failure in Asia at the end of the Cold War - Radchenko, Sergey (Oxford studies in international history, 2014)
Radchenko explores the Asian dimension of Soviet foreign policy during the last decade of the Cold War. He discusses the origins of Soviet rapprochement with China and the reasons for stalemate with Japan, accounts for the failure of the Soviet effort to bring China and India into a strategic alignment with the USSR, and shows how Gorbachev's new thinking conflicted with the geopolitical imperative of maintaining client relationships in the Third World, and how this contradiction tied his hands in Afghanistan, Cambodia, and on the Korean peninsula